Brainstem lesions are associated with sleep apnea in multiple sclerosis. Issue 4 (November 2020) - Levit, Elle; Bouley, Andrew; Baber, Ursela; Djonlagic, Ina; Sloane, Jacob A
Background: Studies linking MRI findings in MS patients with obstructive sleep apnea severity are limited. Objective: We conducted a retrospective study to assess MRI abnormalities associated with obstructive sleep apnea (OSA) in patients with multiple sclerosis (MS). Methods: We performed retrospective chart review of 65 patients with multiple sclerosis who had undergone polysomnography (PSG) for fatigue as well as brain MRI. We measured the number of lesions in the brainstem and calculated the standardized third ventricular width (sTVW) as a measure of brain atrophy, and subsequently performed correlation analyses of the apnea-hypopnea index (AHI) with brainstem lesion location, sTVW, and Expanded Disability Status Scale (EDSS). Results: MS Patients with OSA were significantly older and had a higher body mass index (BMI) and higher AHI measures than patients without OSA. After adjustment for covariates, significant associations were found between AHI and lesion burden in the midbrain (p < 0.01) and pons (p = 0.05), but not medulla. Conclusions: Midbrain and pontine lesions burden correlated with AHI, suggesting MS lesion location could contribute to development of OSA.